Sarcopenia and failure to rescue following liver transplantation. (15th October 2015) - Underwood, Patrick W.; Cron, David C.; Terjimanian, Michael N.; Wang, Stewart C.; Englesbe, Michael J.; Waits, Seth A.
Abstract: Introduction: Sarcopenic liver transplant recipients have higher rates of mortality, but mechanisms underlying these rates remain unclear. Failure to rescue (FTR) has been shown to be a primary driver of mortality following major general and vascular surgery. We hypothesized that FTR is common in sarcopenic liver transplant recipients. Methods: We retrospectively reviewed 348 liver transplant recipients with perioperative CT scans. Analytic morphomic techniques were used to assess trunk muscle size via total psoas area (TPA). One‐yr major complication and FTR rates were calculated across TPA tertiles. Results: The one‐yr complication rate was 77% and the FTR rate was 19%. Multivariate regression showed TPA as a significant predictor of FTR (OR = 0.27 per 1000 mm 2 increase in TPA, p < 0.001). Compared to patients in the largest muscle tertile, patients in the smallest tertile had 1.4‐fold higher adjusted complication rates (91% vs. 66%) and 2.8‐fold higher adjusted FTR rates (22% vs. 8%). Discussion: These results suggest that mortality in sarcopenic liver transplant recipients may be strongly related to FTR. Efforts aimed at early recognition and management of complications may decrease postoperative mortality. Additionally, this work highlights the need for expanded multicenter collaborations aimed at collection and analysis of postoperative complications in liver transplant recipients.